Expression profiling reveals transcriptional regulation by Fbxw7/mTOR pathway in radiation-induced mouse thymic lymphomas - Snijders, Antoine M. (Oncotarget, 2015)
The tumor suppressor gene FBXW7 is deleted and mutated in many different types of human cancers. FBXW7 primarily exerts its tumor suppressor activity by ubiquitinating different oncoproteins including mTOR. Here we used gene transcript profiling to gain a deeper understanding of the role of FBXW7 in tumor development and to determine the influence of mTOR inhibition by rapamycin on tumor transcriptome and biological functions. In comparison to tumors from p53 single heterozygous (p53+/−) mice, we find that radiation-induced thymic lymphomas from Fbxw7/p53 double heterozygous (Fbxw7+/−p53+/−) mice show significant deregulation of cholesterol metabolic processes independent of rapamycin treatment, while cell cycle related genes were upregulated in tumors from placebo treated Fbxw7+/−p53+/− mice, but not in tumors from rapamycin treated Fbxw7+/−p53+/− mice. On the other hand, tumors from rapamycin treated Fbxw7+/−p53+/− mice were enriched for genes involved in the integrated stress response, an adaptive mechanism to survive in stressful environments. Finally, we demonstrated that the Fbxw7 gene signatures identified in mouse tumors significantly overlap with FBXW7 co-expressed genes in human cancers. Importantly these common FBXW7 gene signatures between mouse and human are predictive for disease-free survival in human colon, breast and lung adenocarcinoma cancer patients. These results provide novel insights into the role of FBXW7 in tumor development and have identified a number of potential targets for therapeutic intervention.